The Effect of Parenting, Job Expectancy, And Learning Motivation Towards Students’ Learning Outcomes: Vocational High School - I Made Umbara; I Nyoman Jampel; I Gede Ratnaya; Ni Ketut Widiartini (Universitas Pendidikan Ganesha, 2023)
Both of internal and external factor that have been elaborated above directly influence students’ learning motivation. This study was aimed to analyze the effect of parenting, job expectancy, and learning motivation towards students’ learning outcomes conducted in the form of quantitative research by adapting exp-post facto design. There were 200 students who took accountant major as the research sample. They were selected by using simple random sampling technique. The data were collected through observation, questionnaire distribution, and document analysis. The instruments used were observation sheet and questionnaire. The data were analysed by using Structural Equation Method (SEM-PLS) in which the data were tested through perquisite test. The results showed that; 1) there was a significant effect of parenting towards students’ motivation which directly impacted their learning outcomes, 2) there was a significant effect of job expectancy towards students’ learning motivation which directly influenced their learning outcomes, 3) there was an effect of parenting, job expectancy, and learning motivation towards students’ learning outcomes.